In search of high fired, oxidation glazes - King, Diane (My University, 2006)
Artist Statement My work represents an indirect response to the tactile and visual sensations of the natural world. Of particular interest to me are the reproductive privities of flowers as their forms are both erotically familiar, yet strangely ambiguous when isolated as single specimens. The overlap between the known and the unknown; between what is human and what is flora, is a theme that continues to fascinate me as I consider issues of life and its cycles. Close inspection of flora reveals a rich and varied body of information that is otherwise overlooked by the casual observer. Contrasts of texture and surface detail are hence indicative to my work as referenced by the obsessively carved porcelain as opposed to the coarseness of the terra cotta. A forced intimacy exists between viewer and object due to the diminutive scale of the work.. Therefore interpretation and response is personal, analogous to one’s own visceral reactions to the natural world. Purpose The purpose of this inquiry is to discover suitable glaze coatings that will complement my ceramic work. Due to the delicacy of the forms and the erotic nature of the content, the pieces are constructed from porcelain clay and fired to 2350 degrees Fahrenheit, which in ceramic terms, is referred to as cone 10. Porcelain is a coarse grained, white clay that is very soft and slippery in its moist state. When fired to cone 10, it tightens and approaches a glassy condition known as vitrification (Rhodes, 1998). Consequently, the properties of high-fired porcelain complement both the visual and physical qualities that I seek in my work. However, finishing the pieces with a glaze coating has been difficult. While there are hundreds of cone 10 glazes available to ceramicists, I am specifically searching for glazes that further reveal the texture and sensuality of the work, rather than ones that would completely cover the work. I envision the completed pieces to be subtle in color, with a minimum amount of reflected light. However, most cone 10 glazes are fired in a reduction atmosphere kiln, whereas my work will be fired in an oxidation atmosphere kiln due to studio limitations. Although this is not necessarily problematic, it is an important point to consider when researching glazes. Reduction firing is a process whereby there is a reduced amount of oxygen in the kiln to adequately combust the available fuel. Therefore, any free carbons in the kiln will seize oxygen from any source, including the oxygen present in glaze colorants. The resulting effect is a rich surface in both color and texture. However, in oxidation firing, there is enough oxygen in the kiln to properly combust all of the available fuel. Thus, the colorants or oxides in the glazes are not affected. In the case of oxidation, it is the combination of oxides and fluxes that will cause any variation. Often times, these glazes are not as active or interesting as those of reduction fired glazes (Peterson, 2001; Rhodes, 1998; Rowe,1985). Given these factors, the inquiry into finding appropriate glazes is clear and succinct. I am searching for cone 10, oxidation glazes that are subtle in both color and texture.
This file was last viewed in Adobe Reader 7.0
Keywords: Glazes; Glazing (Ceramics); Ceramic sculpture; Porcelain